Effect of the Friction Coefficient on Clinch Joints - Szabolcs Jónás; Miklós Tisza (International Journal of Engineering and Management Sciences, 2020)
In this study the effect of the friction coefficient on the clinch joints was examined in experimental and numerical way also. The knowledge of the frictional behaviour during the mechanical joining (i.e. clinching) is important from the point of view of resultant geometry which is related to and influence the strength of the joints, and furthermore the maximal forming force is limited by the tool’s failure load which can be reach with a non-favourable frictional condition, as well the aesthetic aspect are also has an importance in some special cases (e.g. in automotive industry).